FUNCTIONAL SCHEME OF INTERACTION OF AIRPORT AIRCRAFT SERVICES IN FAULTY SITUATIONS - Казак, В. М.; Шевчук, Д. О.; Васильєв, М. А. (Science-based technologies, 2012)
In the article reasons of extra situations are analyzed in airport. The main tasks of airport services are analyzed. It is offered count of functioning of airport services in extra weather terms.